Exploring Shareable Contents of Cantonment Public School, College and Govt Zila School in the Field of Education Management - Hasan, K M Zahidul (Yayasan Corolla Education Centre, 2024)
In Bangladesh, there are two common simultaneous branches of education system at secondary levels e.g., Cantonment Public School and College (CPSC) and Govt Zila School (ZS). This study aims to explore the shareable contents of these schooling systems in terms of academic results, co-curricular activities, students’ attendance, and students’ enrollment. To do this, a quantitative research design using a survey questionnaire was employed. A total number of 400 parents and students voluntarily participated in this study. The results explored that there were deviations in the perceptions of parents and students on different aspects of the educational system of these two schools in terms of academic results, co-curricular activities, student attendance, and student enrollment. Nevertheless, the results indicated that some common contents i.e., classroom monitoring, parents’ involvement, and infrastructure are responsible for improving the academic results of these educational systems. The results left insights for teachers, students, policymakers, and researchers.